Microstructure and mechanical properties of AlMo0.5NbTa0.5TiZr lightweight refractory high-entropy alloys fabricated by laser directed energy deposition - Bingbing Sun; Bingqing Chen; Jian Jiang; Xiaolin Bi; Ruifeng Li; Feng Zhang; Lingti Kong; Jinfu Li (Journal of Materials Research and Technology, 2025)
The effects of different laser power parameters and heat treatment processes on the microstructure and mechanical properties of AlMo0.5NbTa0.5TiZr lightweight refractory high-entropy alloys fabricated by laser directed energy deposition were investigated. The results indicate that with the increase of laser power, the area fraction of unmelted particles in the alloy decreases gradually, and the area fraction of unmelted particles remains basically unchanged beyond 1050 W. The fabricated specimen mainly consists of B2+BCC and HCP phases, and its average hardness shows a trend of increasing and then decreasing with increasing laser power, reaching a maximum value of 698.18 HV when the laser power is 1050 W. The compression properties exhibited a non-monotonic trend of decreasing and increasing with the increase of laser power, and the maximum compressive strength is 2473 MPa when the laser power is 1350 W. After heat treatment, the microstructure of the alloy primarily consists of B2, BCC and HCP phases, with partial transformation of the BCC phase into B2 phase. Furthermore, the microhardness and compressive properties of the alloy show a declining trend with increasing heat treatment temperature. Under a fixed heat treatment temperature, the microhardness value of the alloy progressively increased with prolonged holding time.